The intracellular domains of the EphB6 and EphA10 receptor tyrosine pseudokinases function as dynamic signalling hubs. Issue 17 (17th September 2021) - Liang, Lung-Yu; Roy, Michael; Horne, Christopher R.; Sandow, Jarrod J.; Surudoi, Minglyanna; Dagley, Laura F.; Young, Samuel N.; Dite, Toby; Babon, Jeffrey J.; Janes, Peter W.; Patel, Onisha; Murphy, James M.; et al.
Abstract : EphB6 and EphA10 are two poorly characterised pseudokinase members of the Eph receptor family, which collectively serves as mediators of contact-dependent cell–cell communication to transmit extracellular cues into intracellular signals. As per their active counterparts, EphB6 and EphA10 deregulation is strongly linked to proliferative diseases. However, unlike active Eph receptors, whose catalytic activities are thought to initiate an intracellular signalling cascade, EphB6 and EphA10 are classified as catalytically dead, raising the question of how non-catalytic functions contribute to Eph receptor signalling homeostasis. In this study, we have characterised the biochemical properties and topology of the EphB6 and EphA10 intracellular regions comprising the juxtamembrane (JM) region, pseudokinase and SAM domains. Using small-angle X-ray scattering and cross-linking-mass spectrometry, we observed high flexibility within their intracellular regions in solution and a propensity for interaction between the component domains. We identified tyrosine residues in the JM region of EphB6 as EphB4 substrates, which can bind the SH2 domains of signalling effectors, including Abl, Src and Vav3, consistent with cellular roles in recruiting these proteins for downstream signalling. Furthermore, our finding that EphB6 and EphA10 can bind ATP and ATP-competitive small molecules raises the prospect that these pseudokinase domains could be pharmacologically targeted to counter oncogenic signalling.